Phenomic and transcriptomic analyses reveal the sequential synthesis of Fe3O4 nanoparticles in Acidithiobacillus ferrooxidans BYM - Jiani Yang; Shuang Zhang; Yu Zhang; Dan Zhao; Tao Liu; Xindi Sun; Lei Yan (Microbiology Spectrum, 2023)
ABSTRACT Understanding the molecular mechanism of magnetite (Fe3O4) nanoparticle synthesis in Acidithiobacillus ferrooxidans BYM is particularly important for the commercial development of biogenic Fe3O4 nanoparticles. The phenomic parameters such as intracellular iron content and number and size of Fe3O4 nanoparticles were significantly affected by different treatment conditions, i.e., FeSO4·7H2O concentrations (0, 40, and 80 g/L), growth times (12, 36, and 50 h), and magnetic field intensities (0.05, 3.5, and 15 mT) (P < 0.01). Transcriptome analysis revealed that 2,164, 1,587, and 1,061 differentially expressed genes (DEGs) were accordingly detected, and 24 significant expression profiles were identified in A. ferrooxidans BYM under the three treatment conditions. The construction of gene regulatory networks for Fe3O4 nanoparticle synthesis indicated that DEGs mainly enrich ion transport, oxidation-reduction process, membrane structure, signal transduction, and quorum sensing. The four modules were found to be significantly associated with Fe3O4 nanoparticle phenomic parameters using a weighted gene co-expression network. Ten hub genes significantly correlated with Fe3O4 nanoparticle phenomic parameters (P < 0.01) were finally selected from 24 eigengenes related to iron metabolism screened from these models. On the basis of the previous research results and the present study findings, we provide a hypothetical molecular model for Fe3O4 nanoparticle synthesis mediated by these hub genes in A. ferrooxidans BYM comprising membrane formation, iron uptake and transport, iron redox, and crystal maturity. Our results will enable in-depth studies of Fe3O4 nanoparticle synthesis in non-magnetotactic magnetosome-producing bacteria. IMPORTANCE As the most important non-magnetotactic magnetosome-producing bacteria, Acidithiobacillus ferrooxidans only requires very mild conditions to produce Fe3O4 nanoparticles, thus conferring greater flexibility and potential application in biomagnetic nanoparticle production. However, the available information cannot explain the mechanism of Fe3O4 nanoparticle formation in A. ferrooxidans. In this study, we applied phenomic and transcriptomic analyses to reveal this mechanism. We found that different treatment condition factors notably affect the phenomic data of Fe3O4 nanoparticle in A. ferrooxidans. Using transcriptomic analyses, the gene network controlling/regulating Fe3O4 nanoparticle biogenesis in A. ferrooxidans was proposed, excavating the candidate hub genes for Fe3O4 nanoparticle formation in A. ferrooxidans. Based on this information, a sequential model for Fe3O4 nanoparticle synthesis in A. ferrooxidans was hypothesized. It lays the groundwork for further clarifying the feature of Fe3O4 nanoparticle synthesis.